2017
DOI: 10.4236/ijcm.2017.89050
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Attitude and Practice towards Infection Control Measures amongst Medical Students in a Medical Teaching Tertiary Care Hospital

Abstract: Introduction: Health care associated infections (HAIs) are likely to be the most common complication of hospital care. World Health Organization (WHO) estimates these infections to occur among 7% -12% of the hospitalized patients globally, with more than 1.4 million people suffering from infectious complications acquired in the hospital at any time. Keeping this in mind, the present study was conducted to delineate the level of knowledge, attitudes, and practices (KAP) for the use of proper disinfection proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…In a study in Iran, knowledge of 177 nursing students and 162 nursing staff about controlling nosocomial infections was investigated and the results showed that most of nursing staff and students had moderate knowledge [6]. The results of a study in India showed that 75% of the nursing students had good knowledge about the management of nosocomial infections, but their performance was poor [7]. In a study conducted in Jordan (2013), 49.6% of the nursing students had inadequate knowledge about the standards of infection control and 75.9% of them had moderate performance [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a study in Iran, knowledge of 177 nursing students and 162 nursing staff about controlling nosocomial infections was investigated and the results showed that most of nursing staff and students had moderate knowledge [6]. The results of a study in India showed that 75% of the nursing students had good knowledge about the management of nosocomial infections, but their performance was poor [7]. In a study conducted in Jordan (2013), 49.6% of the nursing students had inadequate knowledge about the standards of infection control and 75.9% of them had moderate performance [8].…”
Section: Introductionmentioning
confidence: 99%
“…23 In a similar study, a higher proportion of study participants ensured sterile precautions before catheterization. 24 Most of the doctors' wore gloves regularly for dressing. In another study less proportion of health care workers wore gloves to prevent infection.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Similarly, SCVI is calculated using the number of items in a tool that has achieved a “relevant” rating. [ 13 ] SCV-UA was calculated by adding all items with ICVI equal to 1 divided by the total number of items. The SCVI-Avg was calculated by dividing the sum of the ICVIs by the total number of items.…”
Section: Methodsmentioning
confidence: 99%
“…The SCVI-Avg was calculated by dividing the sum of the ICVIs by the total number of items. [ 13 14 ] An SCVI-UA ≥ 0.8 and an SCVI-Avg ≥0.90 have excellent content validity. [ 14 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation